2006
DOI: 10.1210/jc.2006-0733
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in Childhood and Adolescent Obesity and Its Association with Inflammatory Markers and Components of the Metabolic Syndrome

Abstract: The link between adiponectin levels and a strong marker of inflammation, CRP, is independent of insulin resistance and adiposity in obese children and adolescents. Adiponectin may be one of the signals linking inflammation and obesity. Thus, adiponectin may function as a biomarker of the metabolic syndrome in childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
117
2
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 36 publications
16
117
2
11
Order By: Relevance
“…Recombinant leptin administration has been shown to promote atherosclerosis in mice and endogenous leptin levels have been associated with arterial stiffness, 16 insulin resistance, 12 inflammation, 18 and metabolic syndrome-associated cardiometabolic risk factors 12,14,[17][18][19] in children. Similarly, low levels of adiponectin are mechanistically linked to increased clearance rate of HDL-C (i.e., reduced numbers of this lipoprotein) 25 and are associated with increased progression of coronary artery calcium in adults 11 and increased carotid intima media thickness in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant leptin administration has been shown to promote atherosclerosis in mice and endogenous leptin levels have been associated with arterial stiffness, 16 insulin resistance, 12 inflammation, 18 and metabolic syndrome-associated cardiometabolic risk factors 12,14,[17][18][19] in children. Similarly, low levels of adiponectin are mechanistically linked to increased clearance rate of HDL-C (i.e., reduced numbers of this lipoprotein) 25 and are associated with increased progression of coronary artery calcium in adults 11 and increased carotid intima media thickness in children.…”
Section: Discussionmentioning
confidence: 99%
“…8 Leptin and adiponectin, two of the most abundant adipokines secreted from adipocytes, have been implicated in the development of type 2 diabetes mellitus and cardiovascular disease [9][10][11][12] and are associated with metabolic syndrome, visceral adiposity, insulin resistance, b-cell dysfunction, inflammation, arterial stiffness, and subclinical atherosclerosis in children. 9,[12][13][14][15][16][17][18][19] Leptin plays a prominent role in energy metabolism through its interaction with the hypothalamus and, in the context of obesity, leptin is often produced in high quantities due to leptin resistance. 20 Importantly, leptin is an independent predictor of future weight-gain in obese youth.…”
Section: Introductionmentioning
confidence: 99%
“…40 Hotta et al 41 showed that adiponectin levels in patients with type 2 diabetes mellitus were lower than those of non-diabetic patients, and were particularly low in subjects with coronary artery disease. Winer et al 42 suggested that adiponectin may have a function as a biomarker of MetS in childhood obesity. Ogawa et al 43 have shown that hypoadiponectinemia was associated with visceral fat accumulation and MetS in obese boys.…”
Section: Inflammatory Markers M Gonzá Lez Et Almentioning
confidence: 99%
“…4 Adiponectin is an adipose-tissue-specific, collagen-like protein with important antiatherogenic, antidiabetic and anti-inflammatory properties. [8][9][10] Adiponectin is considered an obesity protection factor and as a biomarker of MetS in children and adolescents. 11 Leptin, a cytokine-like molecule secreted by adipose tissue, regulates adipose mass and body weight by inhibiting food intake and stimulating energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Huber et al reported that CC chemokines such as CCL5 (regulated on activation, normal T cell expressed and secreted; RANTES) are high in obese subjects and that their respective receptors are up-regulated in visceral adipose tissue (VAT) [8]. Recent studies revealed that obesity induces significant changes in the circulating levels of adipocytokines such as adiponectin and tumor necrosis factor in children and adolescents [9][10][11].…”
mentioning
confidence: 99%